ON THE MORPHOLOGY OF ASTHENOHYMEN URALICUM (INSECTA; DIAPHANOPTERIDA: ASTHENOHYMENIDAE) FROM THE LOWER PERMIAN OF THE URALS - Novokshonov V.G.; Willmann R. (My University, 1999)
The body structure of Asthenohymen itralicum G. Zalcssky from the Lower Permian of the Urals, Russia is studied. The male genitalia are described for the first time; the morphology of the head, legs, and ovipositor is investigated in detail. Similarities and differences between asthenohymenids and other diaphanopterids are discussed.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская